Sosialisasi Protokol Kesehatan dan Vaksinasi Penanganan Covid-19 di Desa Mandirancan, Kebasen, Banyumas - Adryan Alif Naufal; Muh. Sulaiman Dadiono (PT. Gyandharma Global Media, 2024)
In 2021, there was an increase in Covid-19 cases in Indonesia due to low public awareness in implementing health protocols, especially the use of masks. The KKN program in Mandirancan Village, Kebasen, Banyumas aims to support efforts to handle Covid-19 through socialization of health protocols as a preventive measure. This activity was carried out using the Participatory Learning and Action method, Participatory Rural Appraisal, and interviews to gather information. This program succeeded in increasing the awareness and response of the Mandirancan Village community to the implementation of the Covid-19 health protocol and vaccination.